THE IMPACT OF TOTAL QUALITY MANAGEMENT (TQM) ON COMPETITIVE ADVANTAGE: A CONCEPTUAL MIXED METHOD STUDY IN THE MALAYSIA LUXURY HOTEL INDUSTRIES - Sin, Kit Yeng; Muhammad Shahar, Jusoh; Noormaizatul Akmar, Ishak (2018)
The widespread use of TQM has impacted the hotel industry worldwide and increasingly identified as the key issue in differentiating service products and building competitive advantage in tourism. Accordingly, hotel industries may face a wide variety of saturated and uncertain TQM practices available for their organization nowadays. As there is a lack of comprehensive knowledge regarding TQM issuesin hotel industry, there is an urgent need for a process which will assist hotel industries in Malaysia to evaluate these TQM practices and select the most appropriate one in order to provide the ideal management practices for the entire organization. As such, this study will propose a mixed method study where 10 hotel managers are initially interviewed, followed by a quantitative study of 122 additional managers. The aim of this study is to assist the hoteliers for identifying the proper TQM practices andthen evaluating the available practices that best fitted the hotel industry in Malaysia which could concomitantly help the Ministry of Tourism and Culture (MOTAC) to achieve its National Key Economic Area (NKEA) and contributing towards high nation incomein 2020.